Changes in blood vitamins A and E, selenium, leukocytes and neutrophil expression of adhesion molecules in dairy cows around parturition (Veterinary Science, 2017)
Blood samples from ten Swedish dairy cows were taken one month before calving, at calving, and one month after calving. The blood concentration of vitamins A and E, and the trace element selenium (Se) were analysed, as well as the total and differential white blood cell counts,a nd the presenceo f CD62L and CD18 adhesionm oleculeso n blood neutrophils. The levels of vitamins A and E decreased significantly at calving, while whole blood Se increased Leukocytosisw as detectedat calving, explainedm ainly by neutrophilia.T he number of lymphocytest endedt o decreasea t calvrng.T he proportion of CD62L- neutrophilsd ecreased sisnlficantlv at this ttme
Keywords: Dairy cows; Immunity; Leucocytes; Vitamins